Temporal and spatial variation of PM2.5 in Antananarivo, the capital city of Madagascar - Mbolanjara Hélène Andriamamonjy; Zo Rakotomavo; Linda Geiser; Lovanomenjanahary Marline (Aerosol and Air Quality Research)
Abstract Madagascar, a low-income country in the Indian Ocean, faces major air quality monitoring challenges due to a limited infrastructure and insuficient data collection. To address this gap, we conduct the first assessment of temporal and spatial variations in fine particulate matter (PM2.5), using Antananarivo as a case study. PurpleAir devices were deployed at seven sites throughout 2023 to monitor PM2.5 concentrations, to identify diurnal and seasonal patterns and to evaluate the influence of meteorological conditions on their variability. Annual PM2.5 concentrations ranged from 21.6 to 31.9 μg m-3, consistently exceeding WHO’s annual guideline (5 μg m-3). Daily concentrations varied from 8.4 to 130.42 μg m-3, with seasonal peaks in October–November (over 70% of days “Unhealthy for sensitive groups”) and in May–June (30%). A bimodal diurnal cycle was observed with elevated PM2.5 concentration in the early morning (02:00–07:00) and evening (14:00–21:00), and a reduced level between 08:00–13:00 during increased atmospheric ventilation index. Meteorological influences on PM2.5 levels were modest but non-negligible. Wind speed exhibits weak negative correlation with PM2.5, consistent with its role in particle dispersion. Relative humidity had a stronger inverse correlation at night and during June to November, suggesting that it promotes particle deposition. Temperature showed seasonal effects, with a positive correlation with PM2.5 concentration in September to February and negative in March to May, likely due to thermal inversions. The ventilation index had a weak impact on PM2.5 variability. These results suggest that PM2.5 variability may be driven by local sources, land use or regional smoke transport than by meteorology alone. This study provides baseline data on air quality in Madagascar and highlights the need for regulatory action, sustainable monitoring and practical tools like moss-bag monitoring alongside future efforts in citizen science and public awareness. Graphical Abstract